2019
DOI: 10.3390/fi11060126
|View full text |Cite
|
Sign up to set email alerts
|

CKMI: Comprehensive Key Management Infrastructure Design for Industrial Automation and Control Systems

Abstract: Industrial Automation and Control Systems (IACS) are broadly utilized in critical infrastructures for monitoring and controlling the industrial processes remotely. The real-time transmissions in such systems provoke security breaches. Many security breaches have been reported impacting society severely. Hence, it is essential to achieve secure communication between the devices for creating a secure environment. For this to be effective, the keys used for secure communication must be protected against unauthori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To increase the security of distributed control systems (DCS), Sergi et al proposed the incorporation of public key infrastructure (PKI), helping to generate a "security by default" implementation scenario [15]. Additional efforts to improve the infrastructure of industrial automation and control systems (IACS) were proposed by Pramod et al [16]. Rezai et al summarized the existing key management schemes in SCADA networks, highlighting issues requiring extensive research, such as cryptographic authority or protocol vulnerability assessments [17].…”
Section: Related Workmentioning
confidence: 99%
“…To increase the security of distributed control systems (DCS), Sergi et al proposed the incorporation of public key infrastructure (PKI), helping to generate a "security by default" implementation scenario [15]. Additional efforts to improve the infrastructure of industrial automation and control systems (IACS) were proposed by Pramod et al [16]. Rezai et al summarized the existing key management schemes in SCADA networks, highlighting issues requiring extensive research, such as cryptographic authority or protocol vulnerability assessments [17].…”
Section: Related Workmentioning
confidence: 99%
“…Preventing attacks against connected devices requires effort from both the industry and users. Vendors must adopt good practices for built-in security measures, such as secure remote access, basic encryption, and patching all known vulnerabilities [39][40][41][42][43][44][45][46][47]. Without proper safeguarding, IP-connected cameras are vulnerable to hacking, which can lead to the compromise of millions of security cameras and video recorders.…”
Section: Security Measures For Vssmentioning
confidence: 99%
“…The industry needs a control system to implement an automation process. This system, the collection of individual control systems and other hardware that automates or operates industrial processes, is identified as the Industrial Control System (ICS refers to [1]). Some industries carry out production activities in several processes at the same time, but in different areas.…”
Section: Introductionmentioning
confidence: 99%